Beneficial effects of the mother's voice on infants' novel word learning. (3rd October 2019) - van Rooijen, Rianne; Bekkers, Eline; Junge, Caroline
Abstract: The maternal voice appears to have a special role in infants' language processing. The current eye‐tracking study investigated whether 24‐month‐olds ( n = 149) learn novel words easier while listening to their mother's voice compared to hearing unfamiliar speakers. Our results show that maternal speech facilitates the formation of new word–object mappings across two different learning settings: a live setting in which infants are taught by their own mother or the experimenter, and a prerecorded setting in which infants hear the voice of either their own or another mother through loudspeakers. Furthermore, this study explored whether infants' pointing gestures and novel word productions over the course of the word learning task serve as meaningful indexes of word learning behavior. Infants who repeated more target words also showed a larger learning effect in their looking behavior. Thus, maternal speech and infants' willingness to repeat novel words are positively linked with novel word learning.